La personalidad y la autoafirmacin en la adolescencia - Varela Ibaez, Julia Isabel (2020)
This learning session entitled "Personality and Self-affirmation in adolescence" it was developed in the area of Personal Development, Citizenship and Civics for fifth grade of Secondary of the Private Educational Institution "Aiapaec". The purpose of this session is that students to analyze some of the theories of personality and evaluate their personal characteristics that make them unique, making an infographic. Through this session, students will learn the main ideas of the theories of personality development raised mainly by the psychologists Sigmud Freud and Erik Erikson.